2002
DOI: 10.1006/viro.2002.1635
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Diversity of the Capsid Gene and the Nonstructural Gene NS2B of Dengue-3 Virus in Vivo

Abstract: Previously, we studied the envelope (E) gene of dengue virus and reported that dengue-3 virus is present as a quasispecies. To investigate the extent of intrahost sequence variation of other dengue viral genes, we examined in this study the capsid (C) gene and the nonstructural gene, NS2B, derived directly from plasma dengue viruses from 18 confirmed dengue-3 patients. Using reverse transcription-PCR, multiple clones of a 360-nucleotide region covering the C gene and of a 404-nucleotide region covering the NS2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
41
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 38 publications
7
41
2
Order By: Relevance
“…3A and C). For the C gene, ten clones from each patient were analyzed as reported previously (26). The mean diversity ranged from 0.13 to 0.41%, and the overall mean diversity was 0.23%, which, in agreement with the results observed for the E gene, was higher than that in the mosquitoes (Table 1).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…3A and C). For the C gene, ten clones from each patient were analyzed as reported previously (26). The mean diversity ranged from 0.13 to 0.41%, and the overall mean diversity was 0.23%, which, in agreement with the results observed for the E gene, was higher than that in the mosquitoes (Table 1).…”
supporting
confidence: 87%
“…We next examined another gene, the C gene, through RT-PCR of a 360-nucleotide region covering the entire C gene ( Fig. 1) (26). Among the 21 clones examined, there were six nucleotide substitutions out of 6,678 nucleotides sequenced, corresponding to a mean diversity of 0.09% (Table 1).…”
mentioning
confidence: 99%
“…The involvement of DI particles has been wellstudied in many RNA viruses, such as LCMV and alphavirus, which leads to virus persistence and increased cytopathology and inflammation. Our study, consistent with previous studies (Wang, Lin et al 2002;Wang, Sung et al 2002), also suggested the DI particles exist in human plasma with dengue viral infection. Combinations of DI particles with standard virus in the viral quasispecies leading to curing of the infection or increasing virus replication remain to be studied.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, truncated HN proteins might be expressed at the surface of the cells and incorporated into newly formed virus particles, possibly with consequences for the binding abilities and the infectivity of the virus (Huang et al , 2004). However, the question arises whether these aberrant and defective genomic RNAs, detected inside the infected cells, are actually packaged into the newly formed virus particles, excreted and transmitted to susceptible hosts, as shown in other models (Cabot et al , 2000;Kissi et al , 1999;Wang et al , 2003). This question could be assessed by studying the virus heterogeneity after virus purification from both organs and cloacal and tracheal swabs.…”
Section: C (1) -----------------------------------------------------mentioning
confidence: 99%